Influence of microbiome and diet on immune responses in food allergy models. (2015) - Barcik, Weronika; Untersmayr, Eva; Pali-Schöll, Isabella; O'Mahony, Liam; Frei, Remo
Abstract : The intestinal immune system is intimately connected with the vast array of microbes present within the gut and the diversity of food components that are consumed daily. The discovery of novel molecular mechanisms, which mediate host–microbe–nutrient communication, have highlighted the important roles played by microbes and dietary factors in influencing mucosal inflammatory and allergic responses. In this review, we summarize the recent important findings in this field, which are important for food allergy and particularly relevant to animal models of food allergy.